Future skills needed for hospitals’ directors in the Kingdom of Saudi Arabia – Applied study on governmental hospitals in Riyadh – - Alotaibi, Majed Muneer; Al-Jarallah, Nasser (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify future skills required for hospital managers in the Kingdom of Saudi Arabia, and the study followed the descriptive analytical approach, where the questionnaire was relied upon as a tool to collect data, and the study community is one of the hospital managers in the Kingdom of Saudi Arabia, and applied to a sample of (200) individuals from various locations in a sample of hospitals. The study reached results, the most important of which is that future skills What is required for the hospital director is primarily time management skills, followed by planning and organizational skills, change management skills, as well as decision-making skills, communication skills, and committee and meeting management skills. In the light of the results, the study recommended the necessity of working on a periodic evaluation of the performance of the hospital director to determine the skills that he possesses and whether they are appropriate for his job location, and the need to work on identifying the training needs of the hospital director and preparing appropriate training and educational programs to develop those skills and refine them in a way that is appropriate for the hospital’s work Administrative and medical.